Pulsating Flow of CNT-Water Nanofluid Mixed Convection in a Vented Trapezoidal Cavity with an Inner Conductive T-Shaped Object and Magnetic Field Effects - Chamkha, Ali J.; Selimefendigil, Fatih; Öztop, Hakan Fehmi (Mdpi, 2020)
Mixed convection of carbon-nanotube/water nanofluid in a vented cavity with an inner conductive T-shaped object was examined under pulsating flow conditions under magnetic field effects with finite element method. Effects of different parameters such as Richardson number (between 0.05 and 50), Hartmann number (between 0 and 30), cavity wall inclination (between 0 degrees and 10 degrees), size (between 0.1 H and 0.4 H) and orientation (between -90 degrees and 90 degrees) of the T-shaped object, and amplitude (between 0.5 and 0.9) and frequency (Strouhal number between 0.25 and 5) of pulsating flow on the convective flow features were studied. It was observed that the average Nusselt number enhanced with the rise of strength of magnetic field, solid nanoparticle volume fraction, and amplitude of the pulsation, while the effect was opposite for higher values of Ri number and cavity wall inclination angle. The presence of the T-shaped object and adjusting its size and orientation had significant impact on the main flow stream from inlet to outlet and recirculations around the T-shaped object and in the vicinity of hot wall of the cavity along with the magnetic field strength. Pulsating flow resulted in heat transfer enhancement as compared to steady flow case for all configurations. However, the amount of increment was different depending on the variation of the parameters of interest. Heat transfer enhancements were 41.85% and 20.81% when the size of the T-shaped object was increased from 0.1 H to 0.4 H. The T-shaped object can be utilized in the vented cavity as an excellent tool for convective heat transfer control. As highly conductive CNT particles were used in water, significant enhancements in the average Nusselt number between 97% and 108% were obtained both in steady flow and in pulsating flow cases when magnetic field was absent or present.
Keywords: mixed convection; pulsating flow; magnetic field; finite element method; T-shaped object